A qualitative inquiry into undergraduates' learning from giving and receiving peer feedback in L2 writing: Insights from a case study. (December 2019) - Cao, Zhenhao; Yu, Shulin; Huang, Jing
Highlights: This study explored fifteen students' perceptions of learning from giving and receiving feedback. Participants exhibited different levels of learning from receiving and giving feedback. Students' engagement with evaluation criteria and motivation for peer feedback mediated student learning. Within-group differences in writing ability and group dynamics could shape student learning from giving peer feedback. Abstract: Although previous research has elaborated on the ways that students can learn from giving or receiving feedback, few qualitative classroom-based studies have examined the ways that students can learn (or not learn) from acting as both a reviewer and a receiver in a feedback group. This qualitative case study focused on the peer feedback experiences and practices of five groups of Chinese EFL university students and explored their perceptions of learning from giving and receiving feedback and the factors that meditated their learning. Data were collected from multiple sources, including drafts of essays, peer feedback, semi-structured interviews, video recordings of peer feedback activities and stimulated recall sessions. The findings showed that the participants perceived different levels of learning from giving and receiving peer feedback and displayed four distinct patterns of value placement: benefit from both giving and receiving feedback, benefit from receiving feedback only, benefit from neither giving nor receiving feedback and benefit from giving feedback only . The participants' learning was mediated by four factors: engagement with evaluation criteria, motivation for peer feedback, within-group differences in writing ability and group dynamics. Situated in an authentic L2 writing context at the tertiary level, this study provides insights into the ways that students learn from (or do not learn from) giving and receiving feedback and the potential factors that promote or limit students' learning from the reciprocal peer feedback process.